2006
DOI: 10.1111/j.1365-2141.2005.05897.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genetic variation in the region of the GPIIIa gene, on PlA2 expression bias and GPIIb/IIIa receptor density in platelets

Abstract: Summary Some studies have suggested that genetic variability in the glycoprotein (GP) IIIa gene modulates expression of platelet GPIIb/IIIa (α2bβ3). We sought to determine as to whether combinations of genetic variants within the GPIIIa gene (haplotypes) influenced the expression of GPIIIa RNA and protein levels in human platelets. Three promoter polymorphisms, PlA1/A2 genotype and platelet receptor densities were determined in 207 acute coronary syndrome (ACS) patients. Allele‐specific quantitative reverse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
(35 reference statements)
3
11
0
2
Order By: Relevance
“…21,22,24,26 Previous studies have found that the levels of ␣ IIb ␤ 3 and glycoprotein (GP)Ib␣ vary over a 2-fold range among normal subjects or patients with ACS. 5,11,[27][28][29] As expected, these increased levels of ␣ IIb ␤ 3 are associated with increased platelet reactivity and decreased sensitivity to ␣ IIb ␤ 3 antagonists. 11,28 Very recently, it has also been shown that the ability of platelets to support thrombin generation may be defined by a subpopulation of larger, perhaps reticulated, platelets bearing nondissociable platelet-derived Factor Va and exhibiting increased adhesion receptor density (P-selectin, GPIb␣, and integrin ␣ IIb ␤ 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22,24,26 Previous studies have found that the levels of ␣ IIb ␤ 3 and glycoprotein (GP)Ib␣ vary over a 2-fold range among normal subjects or patients with ACS. 5,11,[27][28][29] As expected, these increased levels of ␣ IIb ␤ 3 are associated with increased platelet reactivity and decreased sensitivity to ␣ IIb ␤ 3 antagonists. 11,28 Very recently, it has also been shown that the ability of platelets to support thrombin generation may be defined by a subpopulation of larger, perhaps reticulated, platelets bearing nondissociable platelet-derived Factor Va and exhibiting increased adhesion receptor density (P-selectin, GPIb␣, and integrin ␣ IIb ␤ 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative measurements of platelet surface membrane ␣ IIb ␤ 3 among normal subjects, using direct binding of radiolabeled monoclonal antibodies or flow cytometry, have demonstrated a 2-to 3-fold difference, ranging from 25 000 to 75 000 molecules per platelet. [1][2][3][4][5] An allelic variation involving either the ␣ IIb or ␤ 3 gene (ITGA2B and ITGB3, respectively) that can account for this difference has not yet been identified. In the case of ␣ 2 ␤ 1 , the range observed among normal subjects is greater, reported to be as high as 10-fold, and is strongly associated with allelic variants of the ␣ 2 gene ITGA2.…”
mentioning
confidence: 99%
“…The number of adhesion molecules on the platelet surface significantly varies in normal individuals and cardiovascular patients -from about two-fold for GPIIbIIIa [4][5][6][7][8][9][10] and GPIb [6,7,9,[11][12][13], to five-fold for GPVI [14,15] and 10-fold for a2b1-integrin [10,16,17]. Relationships with the intensity of corresponding platelet reactions were demonstrated for GPIIb-IIIa [8,9], GPVI [14,15] and a2b1-integrin [16,18] variations.…”
Section: Introductionmentioning
confidence: 97%
“…Данные о влиянии СОТ на содержание ГП IIb-IIIa соответствуют результатам, недавно опубликованной работы [16], выполненной в сходных группах доноров и пациентов. Отсутствие каких-либо эффектов ГП IIIa Leu33Pro полиморфизма на уровень экспрессии ГП IIb-IIIa подтверждают как наши собственные данные, полученные ранее при исследовании здоровых добровольцев [14], так и данные других авторов [12,13,29,30]. В обеих исследованных нами группах -здоровых добровольцев и больных с ОКС была впервые обнаружена сильная взаимосвязь между СОТ и содержанием еще одного адгезивного рецептора тромбоцитов -ГП Ib.…”
Section: рисунокunclassified
“…Количество молекул клеточной адгезии на поверхности тромбоцитов может значительно варьировать как у здоровых лиц, так и у больных с сердечно-сосудистыми заболеваниями -от двукратных вариаций для ГП IIb-IIIa [10][11][12][13][14][15][16] и ГП Ib [12,13,15,[17][18][19], до 5-кратных -для ГП VI [20,21] и 10-кратных -для a2/b1 интегрина [16,22,23]. Взаимосвязи между содержанием этих молекул и интенсивностью опосредуемых ими тромбоцитарных реакций были продемонстрированы для ГП IIb-IIIa [14,15], ГП VI [20,21] и a2/b1 интегрина [22,24].…”
Section: Introductionunclassified